2013
DOI: 10.1371/journal.pone.0068236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Performance of Multifocal Intraocular Lenses with Same Material Monofocal Intraocular Lenses

Abstract: PurposeTo compare the visual performance of multifocal intraocular lenses (IOLs) and monofocal IOLs made of the same material.MethodsThe subjects included patients implanted with either Tecnis® monofocal IOLs (ZA9003 or ZCB00) or Tecnis® multifocal IOLs (ZMA00 or ZMB00) bilaterally. We conducted a retrospective study comparing the two types of IOLs. The multifocal group included 46 patients who were implanted with Tecnis® multifocal IOLs bilaterally. The monofocal group was an age- and sex-matched control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
59
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 34 publications
(33 reference statements)
9
59
2
5
Order By: Relevance
“…Interestingly, intermediate VA was not impaired in this kind of multifocal IOL. Previous studies showed that with +4.00 D IOLs there is a reduction of intermediate vision, and so +3.00 D IOLs are designed to obtain clear intermediate vision, which can compromise 33 cm near distance vision 1 21. Our results suggested that visual performance was further improved after implantation of ZMB00 IOLs and was consistent with recent report 7 22.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, intermediate VA was not impaired in this kind of multifocal IOL. Previous studies showed that with +4.00 D IOLs there is a reduction of intermediate vision, and so +3.00 D IOLs are designed to obtain clear intermediate vision, which can compromise 33 cm near distance vision 1 21. Our results suggested that visual performance was further improved after implantation of ZMB00 IOLs and was consistent with recent report 7 22.…”
Section: Discussionsupporting
confidence: 92%
“…Multifocal IOL ZMB00 had the same good distance VA as monofocal IOL ZCB00, but much better near VA, which may be because it is pupil-independent, just like previous studies reported 1 2 21. Interestingly, intermediate VA was not impaired in this kind of multifocal IOL.…”
Section: Discussionsupporting
confidence: 62%
“…As demonstrated in other studies, the good quality of distance and near vision was attested through both types of lenses, regardless of which addition had been used. The improvement in UDVA, in addition to the excellent individual results, for both long and short distance confirmed the efficacy of the treatment and provided independence from glasses (1)(2)(3)6,12,13,17,(21)(22)(23)25) . Such inference is particularly evident when considering postoperative SE.…”
Section: Discussionsupporting
confidence: 55%
“…The analysis of groups distribution demonstrates homogeneity and enables comparisons between groups, indicating its suitability for comparison to other publications (7,10,(21)(22)(23)(24) . As demonstrated in other studies, the good quality of distance and near vision was attested through both types of lenses, regardless of which addition had been used.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation